Management control practices in Somalia's traditional clannish society - Hared, Bashir Abdisamad; Abdullah, Zarifah; Rafiul Huque, Sheikh Mohammed (Elsevier Ltd., 2014)
The aim of the study is to report the management control practices (MCP) of a Telecommunication firm operating in Somalia's traditional clannish environment.Through qualitative case strategy, semi-structured interviews, observation and documents analysis were used to gather data.The executive directors of the firm were interviewed. The findings of the study show that MCP of the firm is highly affected by the traditional cultural norms of the Somali clannish society.The prevalent MCP includes “clan business-power sharing”, clan-based ownership, paternal governance, friendship and horizontal relationships, verbal communication and clannish selection of employees.Such MCP has promoted centralized decision making processes in all aspects of the firm's operations.These findings call for further researches.